The Role of the Sidoarjo Regency Transportation Service in Improving Service Quality at Porong Terminal - Inggit Putri Rengganis; Isnaini Rodiyah (Indonesian Journal of Public Policy Review, 2022)
This study aims to describe and analyze the role of the Sidoarjo Regency Transportation Service in improving the quality at Porong Terminal. This type of research uses descriptive qualitative research methods. Data collection techniques using observation, interviews and documentation. The data analysis technique in this study used data collection, data reduction, data presentation and conclusion drawing. The results show that the dimensions of the regulatory role of the Sidoarjo Regency Transportation Service have been going well, including the implementation of the Porong Terminal maintenance program carried out by the Sidoarjo Regency Transportation Service. transportation drivers through vehicle operations that are carried out three to four times a year. Meanwhile, the direct procurement of goods and services from the Transportation Agency of Sidoarjo Regency has not carried out a thorough evaluation of the Porong Terminal. It can be seen from the transportation and prospective passengers who do not take advantage of the main facilities and supporting facilities at Porong Terminal.